The Problem of Theatricality of Russian „new drama” - Шевченко, Елена Н. (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The essay addresses the notion as ‘theatricality’ as such, its historically changing character and its specific qualities concerning the texts of Russian „new drama”. Following M. Lipovetsky, B. Boymers and others the author points out its performative quality, which creates a new type of communication with spectators similar to a ritual act. The author comes to the conclusion that new theatricality of the modern drama asks for reevaluation of traditional approaches to the scenic adaptation of literary material and gives examples proving the possibility of various solutions of this creative task.